Pre-liminary Trial of Pre-sprouted Stump Planting for Artificial Regeneration of Teak - Chaudhari, N.R. (Indian Forester, 1963)
Normal practice for artificial regeneration of teak is planting stumps at the onset of rains. This planting time clashes with the various agricultural operations, causing shortage of labour and resulting in delays. As a solution to these difficulties a preliminary trial of planting of pre-sprouted and pre-established stumps was undertaken so as to take advantage of the growth put on by the established stumps. The trial has been described in brief and tentative conclusions arrived at are enumerated in the article